2015
DOI: 10.1371/journal.pone.0125929
|View full text |Cite
|
Sign up to set email alerts
|

Negative Epistasis between Sickle and Foetal Haemoglobin Suggests a Reduction in Protection against Malaria

Abstract: BackgroundHaemoglobin variants, Sickle (HbS) and foetal (HbF) have been associated with malaria protection. This study explores epistatic interactions between HbS and HbF on malaria infection.MethodsThe study was conducted between March 2004 and December 2013 within the sickle cell disease (SCD) programme at Muhimbili National Hospital, Tanzania. SCD status was categorized into HbAA, HbAS and HbSS using hemoglobin electrophoresis and High Performance Liquid Chromatography (HPLC). HbF levels were determined by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…The differences observed between the protective effects of 3.7-kb alpha-thalassemia against severe bacterial infection contrasts with its deleterious effect against respiratory infections where it appears to favor an increase in the incidence rate. Although this latter result is unexpected, negative epistasis between sickle hemoglobin and 3.7-kb alpha-thalassemia or between sickle hemoglobin and fetal hemoglobin levels resulting in an increased risk of malaria infection have been reported in epidemiologic studies in Kenya (Mmbando et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
“…The differences observed between the protective effects of 3.7-kb alpha-thalassemia against severe bacterial infection contrasts with its deleterious effect against respiratory infections where it appears to favor an increase in the incidence rate. Although this latter result is unexpected, negative epistasis between sickle hemoglobin and 3.7-kb alpha-thalassemia or between sickle hemoglobin and fetal hemoglobin levels resulting in an increased risk of malaria infection have been reported in epidemiologic studies in Kenya (Mmbando et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
“…The present results also fail to compare with conclusions from a study in Mali in which an age stratified analysis showed sickle trait-mediated malaria protection to be more evident in early childhood [ 39 ]. Possible explanations for the lower incidence of uncomplicated malaria among HBB wild types in the current study could relate to protection conferred by fetal hemoglobin and maternal antibodies during early childhood [ 40 42 ]. However the present study did not assess for the levels of fetal haemoglobin and maternal antibodies in infancy, thus other studies would be needed to confirm this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…With regards to understanding mechanisms of protection from sickle haemoglobin (HbS), the programme reported on negative epistasis with fetal haemoglobin (HbF) (Mmbando et al , ). This work proposed that high HbF, which is the aim of hydroxycarbamide treatment for SCD, may result in loss of HbS‐related malaria protection, resulting in higher malaria‐related mortality in SCD.…”
Section: Researchmentioning
confidence: 99%